2018
DOI: 10.1007/s00784-018-2691-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of autofluorescence imaging and histopathological investigation for oral potentially malignant disorders in Taiwan

Abstract: Objectives Autofluorescence imaging is gaining popularity as an adjunctive test for oral potentially malignant disorders (OPMD). This study evaluated the efficacy of autofluorescence imaging based on the current standard oral mucosal disorder checklist in Taiwan. Materials and methods In total, 126 patients suspected to have mucosal disorders at the Division of Oral and Maxillofacial Surgery, Tri-Service General Hospital, Taipei, Taiwan, were enrolled. Following a conventional oral examination by using the ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The detection of OED or discrimination between benign, dysplastic or malignant oral mucosal lesions has been extensively researched, with literature reporting overall poorer specificity along with significant heterogeneity in published studies (Awan & Patil, ; Lingen, Tampi et al, ; Luo et al, ). The results from this review are in keeping with previous studies assessing discrimination between oral mucosal lesions, demonstrating significant heterogeneity and variation in reported efficacy (COE alone: sensitivity: 5.9%–96.6%; specificity: 42.9%–97.8%, OFI alone: sensitivity: 30%–100%; specificity: 12.5%–93%, combined examination: sensitivity: 46%–100%; specificity: 6%–74%; Amirchaghmaghi et al, ; Awan et al, ; Awan et al, ; Babiuch et al, ; Betz et al, ; Chiang et al, ; Farah et al, ; Hanken et al, ; Jayaprakash et al, ; Koch et al, ; Lalla et al, ; Lane et al, ; Marzouki et al, ; Mehrotra et al, ; Moro et al, ; Paderni et al, ; Petruzzi et al, ; Rana et al, ; Sawan & Mashlah, ; Scheer et al, ; Simonato et al, ). It is also interesting to note that all studies with a low risk of bias except Paderni et al reported an overall reduction in specificity using OFI compared to COE alone and at present OFI cannot replace histopathological assessment of a tissue biopsy as the gold standard for the diagnosis of OED or OSCC (Bhatia et al, ; Farah et al, ; Lalla et al, ; Paderni et al, ; Rana et al, ).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The detection of OED or discrimination between benign, dysplastic or malignant oral mucosal lesions has been extensively researched, with literature reporting overall poorer specificity along with significant heterogeneity in published studies (Awan & Patil, ; Lingen, Tampi et al, ; Luo et al, ). The results from this review are in keeping with previous studies assessing discrimination between oral mucosal lesions, demonstrating significant heterogeneity and variation in reported efficacy (COE alone: sensitivity: 5.9%–96.6%; specificity: 42.9%–97.8%, OFI alone: sensitivity: 30%–100%; specificity: 12.5%–93%, combined examination: sensitivity: 46%–100%; specificity: 6%–74%; Amirchaghmaghi et al, ; Awan et al, ; Awan et al, ; Babiuch et al, ; Betz et al, ; Chiang et al, ; Farah et al, ; Hanken et al, ; Jayaprakash et al, ; Koch et al, ; Lalla et al, ; Lane et al, ; Marzouki et al, ; Mehrotra et al, ; Moro et al, ; Paderni et al, ; Petruzzi et al, ; Rana et al, ; Sawan & Mashlah, ; Scheer et al, ; Simonato et al, ). It is also interesting to note that all studies with a low risk of bias except Paderni et al reported an overall reduction in specificity using OFI compared to COE alone and at present OFI cannot replace histopathological assessment of a tissue biopsy as the gold standard for the diagnosis of OED or OSCC (Bhatia et al, ; Farah et al, ; Lalla et al, ; Paderni et al, ; Rana et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…Fifteen studies reported efficacy on detection of OPMD and/or OSCC, with significant heterogeneity and risk of bias noted across the methodologies used (Awan, Morgan, & Warnakulasuriya, ; Betz et al, ; Bhatia et al, ; Cânjău, Todea, Sinescu, Pricop, & Duma, ; Chiang et al, ; Farah et al, ; Koch, Kaemmerer, Biesterfeld, Kunkel, & Wagner, ; Lalla, Matias, & Farah, ; Marzouki et al, ; Moro et al, ; Onizawa, Saginoya, Furuya, & Yoshida, ; Petruzzi et al, ; Sawan & Mashlah, ; Scheer et al, ; Sweeny et al, ). Only three of 15 studies demonstrated low risk of bias across all QUADAS‐2 domains (Bhatia et al, ; Farah et al, ; Lalla et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Standardized forms were used to collect all data. Diagnostic accuracy in terms of the diagnostic odds ratio (DOR), summary receiver operating characteristic (SROC) curve, and area under the SROC curve (AUCs), 1,3,6,12‐35 and the inter‐rater agreement of the autofluorescence analysis, 18,21,36 were analyzed. The screening performance of autofluorescence was compared with that of toluidine blue staining or clinical examination.…”
Section: Methodsmentioning
confidence: 99%